Assessing the health and ecological security of a human induced watershed in central iran - Seyed Hamidreza Sadeghi; Mehdi Vafakhah; Vahid Moosavi; Sanaz Pourfallah Asadabadi; Padideh Sadat Sadeghi; Abdulvahed Khaledi Darvishan; Reza Bagheri Fahraji; Seyed Hossein Mosavinia; Abdolghasem Majidnia; Sudabeh Gharemahmudli; Hamidreza Moradi Rekabdarkolaei (Ecosystem Health and Sustainability, 2022)
Assessment of the watershed health and associated ecological security is crucial for the proper land resources management, notably when sufficient money and time have lacked. The present study aimed to prepare health and ecological security for the Pishkuh Watershed in Yazd Province, central Iran. To prepare the health atlas of the Pishkuh Watershed, the conceptual framework of pressure, state, response (PSR) was employed. The pressure index was investigated by analyzing the driving forces of natural and human-induced factors. Then, the existing conditions of the natural environment and the watershed performance were analyzed using the state index. Besides, the response index was also calculated as a criterion for expressing the degree of community response or different watershed outcomes to the driving forces imposed on the watershed system. The study results revealed that some 91 and 9% of the watershed were classified as moderately healthy and relatively unhealthy. The results of the ecological security index further showed that some 41% of the area was categorized as relatively poor status. The results of the current study can be used by local managers and decision-makers to adaptively designate appropriate, economic, and goal-targeted solutions for the resources management in the region.